The Use of Canagliflozin in Diabetes Mellitus Type 2 on Renal Outcome: A Systematic Review - Haikal, Vikri; Soelistijo, Soebagijo Adi; Puspa; Prajitno, Jongky Hendro (Universitas Airlangga, 2024)
Introduction: One of the leading causes of death in patients with diabetes mellitus is Diabetic Kidney Disease (DKD). Canagliflozin is one of the therapeutic options that can be used to mitigate the progression of DKD. However, the limited existing studies have left the data regarding the effects of canagliflozin on the progression of DKD still unclear. Therefore, a comprehensive study on the efficacy and safety of using canagliflozin in patients with DKD is warranted.Methods: We performed a systematic search in the PubMed, Cochrane Library, ResearchGate, and Springer for randomized, placebo-controlled trials of the treatment of type 2 diabetes mellitus (T2DM) with canagliflozin that were published. A total of 25 journals were identified, and after excluding irrelevant studies, eighteen studies were ultimately included in this systematic review with total participants of 20,047.Results: Canagliflozin reduces the rate of estimated glomerular filtration rate (eGFR) decline in patients with diabetes mellitus. The reduction of urinary albumin-to-creatinine ratio (UACR) level was greater in canagliflozin group than in the control group, and the progression of albuminuria was slower in the canagliflozin group than in the control group.Conclusion: The use of Canagliflozin is considered to be one of the effective therapeutic options for kidney protection in patients with diabetes mellitus who are at risk of chronic kidney disease (CKD).